Electronic Videoendoscopy of Laryngeal Lesions Using a New Type of Rhinolarynx Endoscope Portion. Issue 4 (1998) - Kawaida, Masahiro; Fukuda, Hiroyuki; Kohno, Naoyuki
Abstract : Patients with laryngeal lesions were observed and the lesions were recorded with an electronic videoendoscope system using the PENTAX EPM-3300 video processor and the PENTAX VNL-1330 endoscope portion. The electronic videoendoscope system differs from the conventional fiberoptic endoscope connected to a video camera in that a small monochrome charge-coupled device (CCD) chip is built in the tip of the endoscope portion. The PENTAX VNL-1330 rhinolarynx endoscope portion has a tip and insertion tube of approximately 4mm in outer diameter to allow its introduction through the nasal passages into the larynx. The dynamic color images provided by this system were superior to those obtained by a conventional rhinolarynx flexible fiberscope connected to a video camera in both quality and resolution of detail. This system should be useful in diagnosing laryngeal lesions.